Qualidade da água no reservatório de Alqueva - Rodrigues, Gonçalo (2019)
Monthly in situ measurements obtained in Alqueva reservoir, ongoing since February 2016, of the following parameters were used: Secchi depth and spectral attenuation coefficient. In order to achieve reliable remote detection methods for continuous monitoring and good spatial coverage of physical parameters affecting the water quality of reservoirs such as Alqueva, data obtained from sensors on board satellites such as Sentinel-2 (MSI) were used. To obtain estimates of water quality parameters in Alqueva reservoir, regression analyses were performed between in situ observations and various combinations of spectral reflectances measured by the MSI with atmospheric correction. The water quality parameters were mapped in the Alqueva reservoir in order to have total coverage.